What to Listen for in Music - Copland, Aaron 1900-1990; Rich, Alan; Schuman, William (New York Mentor, 1999)
What to Listen for in Music is a non-fiction book on the subject of music by renowned composer and lecturer Aaron Copland. Compiled from a series of lectures Copland gave in the late 1930s, the book was initially published in 1939, and was later revised into its current form in 1957. Whether they listen to Mozart or Duke Ellington, Copland invites readers to ask two basic questions: Are they hearing everything that is going on? Are they really being sensitive to it? With his provocative suggestions, Copland guides readers through a deeper appreciation of the most rewarding of all art forms.
Includes bibliographical references (p. [246]) and index.
Keywords: Listening; Musical analysis